THE EFFECT OF THE USE OF PORTABLE READING TOOLS ON IMPROVING THE ABILITY TO READ AWARENESS WRITINGS OF LOW VISION STUDENTS - Rohman, Muhamad Hadi; Ehan, E.; Meiyani, Neni (JASSI ANAKKU, 2020)
Low vision learners experience obstacles in reading the writing of caution, this happens also to one of the students who are in SLBN A pajajaran Bandung. With this condition, research creates a plan that aims to improve the ability to read it. In this thesis, researchers tested reading aids to determine the effect of using portable reading lights on improving the reading ability of low vision learners. Research using quantitative approach with Single Subject Research (SSR) method. The design used is A-B design. The subject of the study was a visually impaired student in grade 11 at SLBN A Pajajaran Bandung. Data collection by conducting tests to learners using advanced reading instruments. The data obtained is analyzed through descriptive statistics and displayed in the form of graphs and tables. The results showed a positive influence on improving the ability to read the writing after being given a portable reading light. This can be seen with a stable value at the time of intervention, as well as an increase in the middle value (mean) that is when the baseline phase has a middle value of 27.5% ¬and in the intervention phase has a middle value of 81.25%. The influence can also be seen from the percentage of overlap. The percentage of overlap between the baseline condition and the intervention phase is 0, which means that the smaller the percentage of overlap, the better the effect of the intervention.  Based on the data obtained, the researchers concluded that portable reading lamps can be used for low vision learners who have difficulty reading in low light conditions. Thus, researchers recommend to the school and teachers to provide portable reading light aids to low vision learners to support in learning activities, especially reading writings.